Decentralized Dreams: the Role of Blockchain in Transforming Digital Startups in Iringa Municipal - Kibona, Lusekelo (International Journal of Applied and Scientific Research, 2024)
This study explored the transformative role of blockchain technology in digital startups, focusing on its adoption, impact on operational efficiency, and potential to drive innovation. Utilizing a sample of 95 respondents, the research employed a mixed-methods approach to gather quantitative data and qualitative insights. Key indicators included the adoption of blockchain technology, its effects on operational processes, and its influence on funding mechanisms. Findings revealed a high level of awareness and implementation among startups, indicating that blockchain significantly streamlined processes, enhanced transparency, and fostered innovative business models. However, challenges such as technical difficulties and security concerns were also identified, highlighting the need for ongoing support and education. The study concludes that while blockchain presents substantial opportunities for digital startups, addressing the associated challenges is essential for realizing its full potential.